Enhancing Literacy in Enriching Academic Writing Capacity - Moh. Yamin; Slamet Setiawan (VELES Voices of English Language Education Society, 2019)
This study was conducted to find out the importance of enhancing literacy for enriching the academic writing capacity. The expected study is that it has significance in teaching writing to produce new awareness through literacy and also aims to influence the paradigm in writing use for social practices.  The descriptive qualitative method is applied. The data are taken from four research articles on literacy dealing with academic writing. Findings and results from each research article are the data for this study. Every finding and result of research article becomes the data source to discuss. The findings show that literacy contributes towards the success in academic writing. The good academic writing does not only deal with how the one writes, but also detects whether oneâ€™s writing is the social reflection or not or respond to the social issues or not.